Agrobacterium tumefaciens and its use in plant biotechnology - (:unkn) unknown (Springer Netherlands, 2012)
For years, isolation of foreign genes from one plant and transferring them to another and then observing effects of new genes in transferred plants has only been a dream for a plant biologist. Today, many commercially important species are routinely transformed by different biotechnological methods. Methods available for plant transformation are arranged in three main groups: using biological vectors (virus- or bacteria-mediated transformation), direct DNA transfer techniques (chemical-, electrical-, or laser-induced permeability of protoplasts or cells) and non-biological vector systems (microprojectiles, microinjection or liposome fusion). Today in many countries a number of transgenic important crops such as soybean, maize, cotton, canola, sugarbeet, sugarcane and alfalfa are available and the mostly preferred method is Agrobacterium-mediated transformation. In this chapter, some information about this important bacterium and mechanisms of Agrobacterium-mediated gene transfer are presented. © 2012 Springer Science+Business Media B.V. All rights reserved.
Keywords: Cotton; Crown-gall disease; Molecular marker techniques; T-DNA; Tissue culture; Transgenic; Vir proteins